1994
DOI: 10.2307/1941940
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Rain Forest Conversion to Pasture: Changes in Vegetation and Soil Properties

Abstract: The effects of converting lowland tropical rainforest to pasture, and of subsequent succession of pasture lands to secondary forest, were examined in the Atlantic Zone of Costa Rica. Three replicate sites of each of four land—use types representing this disturbance—recovery sequence were sampled for changes in vegetation, pedological properties, and potential nitrogen mineralization and nitrification. The four land—use types included primary forest, actively grazed pasture (10—36 yr old), abandoned pasture (ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
189
3
21

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(250 citation statements)
references
References 41 publications
37
189
3
21
Order By: Relevance
“…The deforestation of tropical forests alters many soil properties. Previous studies have shown that conversion to pasture causes an increase in pH and soil bulk density as well as a decrease in soil porosity [33][34][35]. As seen in Table 1, the Amazonian soils also have undergone a similar transformation.…”
Section: Model I Of Amazonian Agricultural System: the "Slash-and-burmentioning
confidence: 88%
“…The deforestation of tropical forests alters many soil properties. Previous studies have shown that conversion to pasture causes an increase in pH and soil bulk density as well as a decrease in soil porosity [33][34][35]. As seen in Table 1, the Amazonian soils also have undergone a similar transformation.…”
Section: Model I Of Amazonian Agricultural System: the "Slash-and-burmentioning
confidence: 88%
“…= capacidad de intercambio catiónico. lo observado en el estado de Quintana Roo, México, con respecto a aquellos que han sido impactados por incendios (Sánchez et al, 2007), extracción en selvas húmedas de Australia (Congdon y Herbohn, 1993), y en secuencias de sucesiones forestales de diferentes edades en Brasil (Reiners et al, 1994). En bosques afectados por extracción en el corto (2.5 años) y largo plazo (50 años) estudiados por Seng et al (2004), no se observaron cambios en la composición de las especies.…”
Section: Discussionunclassified
“…Two patterns of changes of N turnover following forest clearing and pasture creation are apparent from previous studies. First, rates of net mineralization and net nitri®cation are consistently lower in soils of pastures 3 yr old or older than in soils of the forests from which they were created (Reiners et al, 1994;Neill et al, 1995Neill et al, , 1997Verchot, pers. comm.).…”
Section: Introductionmentioning
confidence: 99%